Fibers and 3D mesh scaffolds from biodegradable starch-based blends : production and characterization - Pavlov, Miroslav P. (2004)
The aim of this work is the production of fibers from biodegradable polymers to obtain 3D scaffolds for tissue engineering of hard tissues. The scaffolds required for this highly demanding application need to have, as well as the biological and mechanical characteristics, a high degree of porosity with suitable dimensions for cell seeding and proliferation. Furthermore, the open cell porosity should have adequate interconnectivity for a continuous flow of nutrients and outflow of cell metabolic residues as well as to allow cell growth into confluent layers. Blends of corn starch, a natural biodegradable polymer, with other synthetic polymers (poly- (ethylene vinyl alcohol), poly(e-caprolactone), poly(lactic acid)) were selected for this work because of their good balance of properties, namely biocompatibility, processability andmechanical properties. Melt spinning was used to produce fibers fromall the blends and 3Dmeshes fromone of the starchpoly( lactic acid) blends. The experimental characterization includedthe evaluationof the tensilemechanicalpropertiesand thermal properties of the fibers and the compression stiffness, porosity and degradation behavior of the 3Dmeshes.